High Speed Dispensing with Novel 6" Print Head. (November 2016) - Pospischil, M.; Klawitter, M.; Kuchler, M.; Jahn, M.; Efinger, R.; Schwarz, R.; Wende, L.; König, M.; Clement, F.; Biro, D.
Abstract: In this study, a new dispensing print head is introduced covering an operational width of 16 cm and therefore allowing for solar cell processing at industrial throughput rates. Like in previous ten nozzle versions, the interior paste flow was designed by computational fluid dynamics (CFD) using rheological parameters of applied Ag-pastes (commercially available pastes), including yield stress, shear thinning and wall slip behaviour. The novel print head features a homogeneous distribution of Ag-paste from an inlet supply with a diameter of Din = 2mm to an outlet slot with a width of ws = 160 mm. A first printing test followed by geometrical characterization of the dispensed contacts revealed a distribution of the contact finger width of wf = 35±1 μm across the whole wafer (156x156mm 2 ) which demonstrates highest precision of the approach. The print head is directly integrated in an inline feasible dispensing platform, developed by ASYS GmbH. Respective nozzle plates can be customized to any desired front side grid regarding nozzle diameter, nozzle pitch and the total number of nozzles. In the actual version, the print head uses two strokes to print 100 contact fingers. Each of the 50 nozzles prints two adjacent contact fingers while moving up and down at a speed of up to vy = 700mm/s. In a first solar cell test sequence with the new 6" print head, a maximum cell efficiency of η = 21.2% on industrially preprocessed Cz-PERC samples was reached which demonstrates a successful launching of the print head.